The Impact of Sharia Fintech on Financial Inclusion in Indonesia: A Bibliometric Analysis - Nurul Jennah; Taufiqur Rahman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Sharia FinTech is the integration of financial technology with Islamic financial principles, which plays a role in increasing financial inclusion in Indonesia. This study aims to analyze the impact of Sharia FinTech on financial inclusion using a bibliometric approach. The research data was obtained from Google Scholar in the period 2015 to 2025, which was then analyzed using VOSviewer software to visualize publication trends and relationships between concepts. The results of the study indicate that Sharia FinTech, especially in the form of sharia P2P lending and waqf-based crowdfunding, plays an important role in expanding access to financial services for previously underserved communities. The main factors driving the growth of Sharia FinTech include increasing internet penetration, smartphone usage, supportive government policies, and sharia regulations that ensure the conformity of the digital financial ecosystem with Islamic principles. This study also identified that research on the analysis of the impact of Sharia FinTech on financial inclusion still has room for further exploration. The implications of this study can be a basis for academics and practitioners in developing research and policies that support sharia-based financial inclusion in the future.